The Effectiveness of Text Message Reminder- Recalls on Human Papilloma Virus Vaccination Coverage in Georgia - Tamira Moon; Nicolle Dally; Ben Sloat; Kia Bryant; Sherrionda Grady (Georgia Southern University, 2016)
Background: Routine vaccination against Human Papilloma Virus (HPV), the main cause of cervical cancer, is recommended by the Advisory Committee on Immunization Practices for adolescents ages 11 to 12 years, yet vaccine coverage remains low. The Georgia Comprehensive Cancer Control Program and Georgia Immunization Program implemented and evaluated a textmessaging campaign aimed at improving HPV vaccination coverage, using the Georgia Immunization Registry (GRITS). Methods: The text message reminder-recall campaign, aimed at the parents of adolescents 9 - 18 years, was launched in July 2015. A total of 208,792 adolescents in the GRITS database met the inclusion criterion, receipt of at least one dose of the threedose series HPV vaccine. We determined the rate of HPV vaccine series completion for adolescents with a valid parent/guardian mobile phone number and for those without. Results: A total of 9,711 text messages were successfully sent to parents of adolescents 9 - 18 years. HPV vaccine series completion was 16% among adolescents whose parent/guardian received a text message as compared to 7% among those who did not. Conclusions: Text message reminder-recalls have a positive effect on HPV vaccine series coverage for adolescents in Georgia. Text messaging reminder-recalls may be an effective strategy to improve HPV vaccination coverage statewide.